Incremental quality improvement in web applications using web model refactoring - Olsina Santos, Luis Antonio (^p Datos electrónicos (1 archivo : 365 KB))
Web applications must be usable and accessible; besides, they evolve at a fast pace and it is difficult to sustain a high degree of external quality. Agile methods and continuous refactoring are well-suited for the rapid development of Web applications since they particularly support continuous evolution. However, the purpose of traditional refactorings is to improve internal quality, like maintainability of design and code, rather than usability of the application. We have defined Web model refactorings as transformations on the navigation and presentation models of a Web application. In this paper, we demonstrate how Web model refactorings can improve the usability of a Web application by using a mature quality evaluation approach (WebQEM) to assess the impact of refactoring on some defined attributes of a Web product entity. We present a case study showing how a shopping cart in an e-commerce site can improve its usability by applying Web model refactorings. -- Keywords: refactoring, Web applications, usability, quality evaluation.